2022
DOI: 10.3390/cancers14112656
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Gut Microbiota with Endocrine Homeostasis and Thyroid Cancer

Abstract: The gut microbiota plays a crucial role in healthy individuals as well as in patients with thyroid diseases, including thyroid cancer. Although the prognosis of differentiated thyroid cancer is predictable, that of some poorly differentiated, medullary, and anaplastic thyroid cancers remains unpromising. As the interaction between the gut microbiota and thyroid cancer has been gradually revealed in recent years, the thyroid gland, a crucial endocrine organ, is shown to have a complex connection with the body’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“… The very few studies available seem to indicate the reduction of the butyrate-producing gut microbiota as potential signature of thyroid cancer. The same SCFA by inhibiting histone deacetylase, seems to activate NIS re-expression in thyroid cancer cells, inducing iodine uptake and redifferentiation [ 20 , 22 , 25 , 40 , 41 , 45 , 48 ] Is there an impact of gut microbiota composition in micronutrients related to thyroid homeostasis? The link between micronutrients homeostasis and gut microbiota composition is complex and bidirectional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… The very few studies available seem to indicate the reduction of the butyrate-producing gut microbiota as potential signature of thyroid cancer. The same SCFA by inhibiting histone deacetylase, seems to activate NIS re-expression in thyroid cancer cells, inducing iodine uptake and redifferentiation [ 20 , 22 , 25 , 40 , 41 , 45 , 48 ] Is there an impact of gut microbiota composition in micronutrients related to thyroid homeostasis? The link between micronutrients homeostasis and gut microbiota composition is complex and bidirectional.…”
Section: Resultsmentioning
confidence: 99%
“…An excess of iron intake may favor the increase of intestinal pathogens [ 15 , 18 , 19 , 22 , 24 , 26 , 27 , 29 32 , 34 , 39 , 46 ] Is there a rationale for the use of probiotics, prebiotics or synbiotic in unselected patients with thyroid disorders? There are no evidence supporting the routine use of probiotics, prebiotics or synbiotic in unselected patients with thyroid disorders [ 13 , 15 , 18 , 20 , 22 , 23 , 25 , 26 , 34 , 35 , 38 , 40 , 46 , 48 , 49 ] Should a specific diet be suggested to patients with thyroid disorders? Despite dietary habits represents one of the major determinant in microbiota shaping, the evidence of a specific interplay between diet, gut microbiota and thyroid disorders is still scanty.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the biomolecule lipopolysaccharide (LPS) stands out, which is part of the cell wall of Gramnegative bacteria and is a trigger of septic shock. It was stated that LPS "is no less endotoxin than an exohormone", showing that LPS has similarities to human hormones, for example, LPS has its exposure dependent on endogenous reserves (commensals, Gram-negative bacteria of the gastrointestinal tract ), has a transporter protein, interacts with the specific cell receptor, its signaling is specifically modulated by endogenous mechanisms, and the LPS signal interferes with endogenous hormone pathways [13].…”
Section: Resultsmentioning
confidence: 99%
“…A number of clinical studies suggested a strong correlation between exposure to environmental pollution and the incidence and mortality rates of cancer [ [16] , [17] , [18] ], which was consistent with results in animal models [ 19 , 20 ]. In addition, a series of studies have revealed that the disruption of the endocrine system plays significant roles in the development of breast cancer [ 21 ], prostate cancer [ 22 ], thyroid cancer [ 23 ], and endometrial cancer [ 24 ]. Moreover, endocrine therapy has been tried to treat these cancers mentioned above.…”
Section: Introductionmentioning
confidence: 99%